2015
DOI: 10.1200/jco.2015.62.3397
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Antitumor Activity of Anti–PD-1 Antibody, Nivolumab, in Patients With Platinum-Resistant Ovarian Cancer

Abstract: This study, to our knowledge, is the first to explore the effects of nivolumab against ovarian cancer. The encouraging safety and clinical efficacy of nivolumab in patients with platinum-resistant ovarian cancer indicate the merit of additional large-scale investigations (UMIN Clinical Trials Registry UMIN000005714).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
768
1
8

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 988 publications
(799 citation statements)
references
References 33 publications
22
768
1
8
Order By: Relevance
“…Remarkably, in a recent study, the clinical efficacy of an anti-PD-1 mAb has been reported in patients with ovarian carcinoma. 66 It is possible that the beneficial effects documented in this study might reflect not only a blockade of PD-1/PD-L on tumor-infiltrating lymphocytes but also on PD-1 1 NK cells.…”
Section: Discussionmentioning
confidence: 96%
“…Remarkably, in a recent study, the clinical efficacy of an anti-PD-1 mAb has been reported in patients with ovarian carcinoma. 66 It is possible that the beneficial effects documented in this study might reflect not only a blockade of PD-1/PD-L on tumor-infiltrating lymphocytes but also on PD-1 1 NK cells.…”
Section: Discussionmentioning
confidence: 96%
“…Immunotherapy using antibodies targeting checkpoint proteins has become of increasing interest and a number of clinical trials using these antibodies for several different cancer types have shown clinical responses 22, 23, 24, 25, 26, 27, 28. However, studies with animal models and cancer patients have also shown that combining antibody blockade of the PD‐1/PD‐L1 axis with other forms of immunotherapy can lead to more meaningful clinical responses 32, 33, 34, 35.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, pembrolizumab treatment of patients with PD‐L1‐positive advanced non‐small‐cell lung cancer prolonged their overall survival 25. Using a different PD‐1 blockade antibody, nivolumab, clinical efficacy was shown for patients with metastatic renal cell carcinoma and for patients with ovarian cancer 26, 27. Nivolumab also increased survival of patients with non‐squamous non‐small‐cell lung cancer that resisted prior chemotherapy 28.…”
Section: Introductionmentioning
confidence: 99%
“…Some phase Ib-II trials have investigated the activity and safety of anti-PD1 or anti-PD-L1 mAbs in platinum-resistant EOC, with objective response (OR) (complete response (CR)+ partial response (PR)) rates ranging from 5.9% to 15% (22,(39)(40)(41) and with grade (G)≥3 AE rates ranging from 3.8% to 40% (Table I). Nivolumab obtained an OR and a disease control (CR+PR+stable disease (SD)) in 15% and 45% of 20 patients who had received at least two prior chemotherapy lines (39) ( Table I).…”
Section: Epithelial Ovarian Cancermentioning
confidence: 99%